Chung Sang-Hwa - Griffin, Tim 19XX- (Dominique Lévy, 2016)
Working since the late 1960s, Korean artist Chung Sang-Hwa (born 1932) has used the canvas as a site for ritual and process, typified in the 1973 masterpiece "Untitled 73-12-11" a tall canvas comprised of faint vertical white and gray lines. This volume includes an essay by Tim Griffin, a poem by Yuko Otomo and a comprehensive chronology. Exhibition: Dominique Lévy Gallery, New York City, United States (01.06.-30.07.2016) / Greene Naftali Gallery, New York City, United States (01.06.-30.07.2016)
Published on the occasion of "Chung Sang-Hwa", June 1-July 30, 2016, Dominique Lévy, New York, Greene Naftali, New York
Keywords: Jeong, Sang hwa -- 1932-; Chung, Sang Hwa / 1932- / Exhibitions; Chung, Sang Hwa / 1932-; Exhibition catalogs; Ausstellungskatalog; Ausstellungskatalog -- Dominique Lévy -- 01.06.2016-30.07.2016 -- New York, NY; Ausstellungskatalog -- Greene Naftali -- 01.06.2016-30.07.2016 -- New York, NY; Bildband